PERLINDUNGAN BAGI KELOMPOK AGAMA MINORITAS MENGHADAPI KELOMPOK AGAMA MAYORITAS: STUDI KASUS AHOK DAN MELIANA - Elisabeth Sundari; Anna Marieta Simangunsong; Isabelle Valerie; Matheus Nurlatu (Justitia et Pax, 2020)
Through the case studies, Ahok and Meliana, this research aims to explain how the religious minority try to obtain protection to fulfill human rights when faced with religious majority pressure from the majority group. Normative research will answer the problem by analyzing the process of prosecution, the adjudication, and the punishment for Ahok & Meliana and the demonstration both outside the court and in the trial process demanding severe punishment for the accused of religious blasphemy. The result shows that even though it is difficult to prove directly, the mobilization of the masses in the judicial process can affect judges' independence to provide protection and justice for religious minority. The case of Ahok and Meliana shows how difficult it is for minority religious groups to seek protection against pressure from the majority religious groups because the State and Judges cannot prevent and take firm action against mass pressure from the majority religious groups against minority religious groups. The case such as Ahok and Meliana will occur as long as blasphemy's criminalization is still in effect. If the principle of non-discrimination or commutative justice is applied, and not the principle of protection based on 'partiality for the vulnerable,' the protection for religious minority groups will not be realized fully.